Natural Dyes from Chlorella Vulgaris sp Extracted via Supercritical Fluid Extraction Dyed on Silk Fabric - F. Che Rahim, A.; R. Ahmad, M.; Ismail, K.; I. Ab Kadir, M. (International Journal of Engineering and Technology, 2019)
Of late, research on natural dyes is increasing due to its eco-friendly and less hazardous nature towards humankind. This study focuses on the colour coordinates and colour strength of dyes from Chlorella Vulgaris sp extracted via Supercritical Fluid Extraction (SFE). The SFE optimum parameters for yield extracts were obtained through response surface methodology along with central composite design approach. Exhaustion dyeing with meta-chrome method was performed on silk fabrics for 60 minutes at 85oC. The dyed silk fabrics were measured and analysed for their colourimetric and fastness properties in accordance to MS ISO and AATCC standards, respectively. The colour shades on the dyed silk fabrics using alum mordant were light brown while for the iron mordant were dark brown. These shades were confirmed with the colour coordinates, L*a*b*, values of the fabrics. The colour strengths of the fabrics dyed with the iron mordant at 2% and 5% dyes were the highest in comparisons with other dyed fabrics. Overall, the colourfastness of the fabrics to washing were quite low but with very good colour staining ratings and fastness to perspiration, rubbing and light.Â Â